Long-term Follow-up of Patients Undergoing Nephrectomy for Urolithiasis - Thiago Augusto Cunha Ferreira; Alexandre Danilovic; Samirah Abreu Gomes; Fabio Carvalho Vicentini; Giovanni Scala Marchini; Fábio César Miranda Torricelli; Carlos Alfredo Batagello; William Carlos Nahas; Eduardo Mazzucchi (International Brazilian Journal of Urology)
ABSTRACT Purpose: This prospective study aimed to identify risk factors associated with progression to stage 3 chronic kidney disease (CKD) and the occurrence of kidney stone formation or growth following nephrectomy for urolithiasis. Materials and methods: From January 2006 to May 2013, patients undergoing nephrectomy for urolithiasis were enrolled. Renal function was assessed using estimated glomerular filtration rate (eGFR) via the Chronic Kidney Disease Epidemiology Collaboration equation, while kidney stone events were detected using computed tomography. Results: Among 107 patients followed for an average of 83.5 months, type 2 diabetes mellitus (T2DM) significantly increased the risk of progression to stage 3 CKD by 34.79-fold (p=0.004). Age was associated with a 15% increase in the odds of developing stage 3 CKD per year (p=0.01), while higher preoperative eGFR was protective (OR=0.84, p<0.01). DMSA-99mTc values below 15% were less likely to lead to renal function deterioration. New kidney stone formation occurred in 15.9% of patients and stone growth observed in 12.1%. Contralateral kidney stones (p<0.01) and hypercalciuria (p=0.03) were identified as risk factors for kidney stone events. Conclusions: T2DM and age were predictors of CKD progression, while higher preoperative eGFR was protective. Hypercalciuria and contralateral kidney stones increased the risk of kidney stone formation and/or growth post-nephrectomy for urolithiasis.